The Characteristics of Preeclampsia with Severe Features - Adjie, JM Seno; Lisnan, Fredy; Sutandar, Yosep (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: To describe the characteristics of preeclampsia with severe features and their risk factors. Method: This study was a retrospective medical record review of demographic characteristics, obstetric and medical data of preeclampsia with severe features in Dr. Cipto Mangunkusumo Hospital from July to December 2014. Result: There were 1,013 deliveries which 183 patients of them were diagnosed as preeclampsia with severe features (18.06%). The study showed 67.76% were 20 - 35 years old, most of them were multiparity, and 41.53% were preterm labor with 28 - 336 weeks of gestation then followed by 24.59% were 34 - 366 weeks’ gestation. Majorities of preeclampsia with severe features patients were without complication either to the mother or the baby. There were 1 case of maternal mortality and 15 cases of intra uterine fetal death (IUFD). There were 73.77% cases delivering by cesarean section. The complication of the mother in preeclampsia with severe features was related significantly to the complication in baby, such as preterm delivery. Besides, women’s age and parity had significant relationship with baby complication. Conclusion: There is association of complication in preeclampsia with severe features women with baby, namely preterm delivery. Besides, women’s age and parity is related to complication of baby. Keywords: complication, preeclampsia, risk factors